O conceito constitucional de dependência econômica na pensão por morte - Simonato, Priscilla Milena (2012)
This dissertation talks about the concept of economic dependence for getting the pension benefit for death. It aims to analyze who the insured s economic dependents are, according to the Federal Constitution. The pension benefit for Death, constitutionally provided, as well as listed in an ordinary law n. º 8.213/91, is a social security benefit granted to the insured dependents. However, the common law has created an exhaustive list of dependents who have the real social security benefits in case of death risk. This list of dependents, besides having the reliant presumption, violates, in many cases, the constitutional principles about the social justice and exact application of the principle of human dignity, which is a fundamental right and lead us to search the real concept of economic dependence through a constitutional interpretation